El uso del color en la comunicación visual de las estrategias de persuasión política: caso de estudio votantes entre 18 a 40 años participantes de las elecciones seccionales de las parroquias Sucre y San Sebastián de la ciudad de Loja, 2023 - Armijos Jiménez, Josselyn Anahí (2024)
This research focused on analysing how the use of colour in visual communication is part of political persuasion strategies: case study of voters between 18 and 40 years old participating in the sectional elections in the parishes of Sucre and San Sebastián in the city of Loja, 2023. It was developed using a mixed approach applying surveys to the population and interviews with experts and stakeholders on the issue of colour and its impact on voters. The methods used succeeded in extracting the population's perception of colours that can generate two types of functions in our brain: adaptation, which are stimulating and exciting, and opposition, which are calming. In addition, the extent to which the population is sensitive to the stimulus that the colours used by the parties have on their voting intentions. The findings highlight that the majority of respondents do not believe that the colours used in election campaigns have an effect on their voting decision. This suggests that the influence of colours on decision making appears to be limited, which means that strategies based on the use of colours may not be as effective. Against this, the findings reflect the complexity of political communication, where voters' perceptions and experts' perspectives can differ significantly. Voting decision making is a process influenced by emotional factors, although colours can play a crucial role in the perception and coherence of political campaigns.